Shape grammars for creative decisions in the architectural project - Tching, J. (2017)
Shape grammars (SG), which define a set of shapes, are used in applications in the field of Computational Creativity (CC). Computational Creativity can be considered an area of Artificial Intelligence (AI) that chases the goal of understanding creativity and building computational applications that emulate or support human creativity in Arts and Science. In this context, our aim is to show how SG may provide artists with applications to assist them in the creative process, not only creating solutions but also as a way of creating new ideas. Our objective is to demonstrate how, in architecture, SG can work with rules that will convey legal restrictions, space needs and goals of the architect, creating possible solutions to a project. A wide range of solutions can be tested in computational applications based in SG. These applications can also encourage the architect to go further in his creativity through shape emergence where the conditions are fulfilled and presented as innovative and/or unexpected. Architects obey strict rules when they apply artistic intention to a specific need/objective intention (space building). Thus, our methods are to enumerate SG as a tool for decision-making in architectural projects and to show a set of common phases that may be generated by the use of computational applications in response not only to technical needs but also to creative goals.